Singlet Fission in Concentrated TIPS-Pentacene Solutions: The Role of Excimers and Aggregates - Dvořák, Miroslav; Prasad, Shyamal K K; Dover, Cameron B; est, Chelsea R; Kaleem, Akasha; MacQueen, Rowan W; Petty, Anthony J; ecast, Roslyn; Beves, Jonathon E; Anthony, John E; Tayebjee, Murad J Y; Widmer-Cooper, Asaph; et al. (Journal of the American Chemical Society, 2021)
The excited-state dynamics of 6,13-bis(triisopropylsilylethynyl)pentacene is investigated to determine the role of excimer and aggregate formation in singlet fission in high-concentration solutions. Photoluminescence spectra were measured by excitation with the evanescent wave in total internal reflection, in order to avoid reabsorption effects. The spectra over nearly two magnitudes of concentration were nearly identical, with no evidence for excimer emission. Time-correlated single-photon counting measurements confirm that the fluorescence lifetime shortens with concentration. The observed rate constant grows at high concentrations, and this effect is modeled in terms of the hard-sphere radial distribution function. NMR measurements confirm that aggregation takes place with a binding constant of between 0.14 and 0.43 M-1. Transient absorption measurements are consistent with a diffusive encounter mechanism for singlet fission, with hints of more rapid singlet fission in aggregates at the highest concentration measured. These data show that excimers do not play the role of an emissive intermediate in exothermic singlet fission in solution and that, while aggregation occurs at higher concentrations, the mechanism of singlet fission remains dominated by diffusive encounters.The excited-state dynamics of 6,13-bis(triisopropylsilylethynyl)pentacene is investigated to determine the role of excimer and aggregate formation in singlet fission in high-concentration solutions. Photoluminescence spectra were measured by excitation with the evanescent wave in total internal reflection, in order to avoid reabsorption effects. The spectra over nearly two magnitudes of concentration were nearly identical, with no evidence for excimer emission. Time-correlated single-photon counting measurements confirm that the fluorescence lifetime shortens with concentration. The observed rate constant grows at high concentrations, and this effect is modeled in terms of the hard-sphere radial distribution function. NMR measurements confirm that aggregation takes place with a binding constant of between 0.14 and 0.43 M-1. Transient absorption measurements are consistent with a diffusive encounter mechanism for singlet fission, with hints of more rapid singlet fission in aggregates at the highest concentration measured. These data show that excimers do not play the role of an emissive intermediate in exothermic singlet fission in solution and that, while aggregation occurs at higher concentrations, the mechanism of singlet fission remains dominated by diffusive encounters.